End of the upswing in Euroland: No reason to cut interest rates - Christophe Kamps; Joachim Scheide (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2001)
Economic expansion in Euroland has decelerated considerably after mid-2000 as a consequence of the weakening of growth in the world economy, the tightening of monetary policy by the European Central Bank as well as the burden imposed by higher oil prices. While the upswing in the euro area has come to an end, there is no reason to dramatize the current situation. It has to be kept in mind that economy-wide capacity utilization has already risen to its normal level, and it is not likely that real GDP will fall below potential output. The government budget of euro-area countries showed a surplus in 2000 for the first time since the 1960s. This year and next year the euro-area budget will change into a deficit also because taxes had been cut in a number of countries. It has to be criticized that consolidation efforts have ceased; in particular Germany, France, and Italy are still far away from a balanced budget. There is a risk that these countries will not meet their targets; the stability and growth programs are somewhat unrealistic because governments expect that higher trend growth than in the past will solve the problem. Many observers have urged the ECB to follow the example of the Fed and cut interest rates in order to prevent a sharp drop in economic activity. But in our view the ECB neither should nor will alter its course. First of all the current stance of monetary policy is not restrictive; according to the Taylor rule, short-term interest rates are even too low. Moreover, the growth of M3 will not fall below the reference value. Finally, the projections presented by the ECB last December do not justify a cut in interest rates. In the medium run, the expansion of the money stock is the most important factor for inflation, while in the short run inflation is also influenced by other factors. These considerations underlie the P-star model in which the development of inflation depends on the liquidity overhang, defined as price gap, as well as on cost factors. This model can explain the past movements of inflation quite well. As regards the inflation forecast it is important to note that the price gap has closed due to a rise in the price level and the slower increase in M3 in the past months. Consequently, we expect that the increase in consumer prices will gradually slow in 2001 and 2002. Recently, the Irish government has been criticized by the Council of European finance ministers for its fiscal policy. This came as a surprise in view of the excellent situation of public finances in Ireland. The critique aimed at the loosening of fiscal policy which would aggravate the bottlenecks in the economy. But it is also questionable whether a fiscal contraction in Ireland would be the appropriate response. All in all, the only way to cool down the economy seems to be an acceleration of wage growth and inflation and the implied real appreciation of the Irish pound.
Keywords: 330; Konjunktur; Konjunkturprognose; Zinspolitik; Europäische Wirtschafts- und Währungsunion; EU-Staaten